2008
DOI: 10.1152/ajpendo.90208.2008
|View full text |Cite
|
Sign up to set email alerts
|

Transient prenatal androgen exposure produces metabolic syndrome in adult female rats

Abstract: Androgen exposure during intrauterine life in nonhuman primates and in sheep results in a phenocopy of the reproductive and metabolic features of polycystic ovary syndrome (PCOS). Such exposure also results in reproductive features of PCOS in rodents. We investigated whether transient prenatal androgen treatment produced metabolic abnormalities in adult female rats and the mechanisms of these changes. Pregnant dams received free testosterone or vehicle injections during late gestation, and their female offspri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
110
7
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(130 citation statements)
references
References 40 publications
10
110
7
3
Order By: Relevance
“…A study of female sheep prenatally treated with testosterone found increased mRNA expressions of the IRS1 and GSK3 genes in skeletal muscles and the IRS2, PI3K, and AKT genes in adipose tissue (Nada et al 2010). In a rodent study, no difference was found in the expression levels of the IR, IRS1, IRS2, and AKT proteins in the skeletal muscles or liver, after prenatal testosterone exposure (Demissie et al 2008). These conflicting observations may result from differences between the action of DHT and testosterone, interspecies differences, and the expression of phosphorylated protein distinct from mRNA in insulin signaling pathway.…”
Section: Discussionmentioning
confidence: 98%
“…A study of female sheep prenatally treated with testosterone found increased mRNA expressions of the IRS1 and GSK3 genes in skeletal muscles and the IRS2, PI3K, and AKT genes in adipose tissue (Nada et al 2010). In a rodent study, no difference was found in the expression levels of the IR, IRS1, IRS2, and AKT proteins in the skeletal muscles or liver, after prenatal testosterone exposure (Demissie et al 2008). These conflicting observations may result from differences between the action of DHT and testosterone, interspecies differences, and the expression of phosphorylated protein distinct from mRNA in insulin signaling pathway.…”
Section: Discussionmentioning
confidence: 98%
“…PCOS is the number one cause of infertility in premenopausal women, and frequently women with PCOS have metabolic diseases such as hypertension and insulin resistance [1]. Interestingly, treatment of various animals prenatally with testosterone produces the metabolic as well as reproductive disorders associated with PCOS [2][3][4][5][6][7][8][9]. The metabolic defects associated with prenatal androgen exposure are not limited to females, but are also seen in males [2,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of androgens on lipid metabolism was also demonstrated in female rats under prenatal androgen treatment, which developed dyslipidemia and hepatic steatosis in adulthood. These changes would be the consequence of increased adipose tissue and insulin resistance induced by prenatal androgenization (Demissie et al 2008). A similar metabolic alteration has been described in adult rats following early postnatal administration of testosterone (Alexanderson et al 2007).…”
Section: Discussionmentioning
confidence: 60%